Peran penting manajemen dalam menghadapi pengaruh lingkungan bisnis: Kunci kesuksesan organisasi di era globalisasi - Hidayah, Syifaul Awwalina (Maliki Interdisciplinary Journal, 2025)
In an era of globalization marked by rapid technological change and market dynamics, organizations are required to have a high level of adaptability in order to survive and thrive. This article discusses the strategic role of management in responding to the influence of an organization’s internal and external environments. The internal environment includes human resources, organizational structure, corporate culture, and physical and financial assets, while the external environment includes economic, political, social, technological, and cultural factors. Through the SWOT analysis approach, organizations can formulate strategies that are aligned with internal strengths and external opportunities, while anticipating weaknesses and threats. The discussion also covers the importance of change management, competitive strategy, stakeholder management, and risk management as part of the response to environmental dynamics. The results of the study show that effective, proactive, and strategic management is the key to achieving competitive advantage and organizational sustainability amid global challenges.